(untitled) (Cadernos de Sociomuseologia, 2012)
The present paper discusses the complex understanding of Museum as an entity that provides services. Indeed we are far from seeing museums fully acting as services since the rationale of the way they operate derives from the permanent concession of grants either from state budgets or from beneficent institutions. In order to do this, we use reflections presented in previous papers, where we considered these issues separately; we now believe they will gain some coherence when articulated with the reflection on museums seen in their possible, albeit inadequately assumed, condition as service providers.We shall consider some aspects of the introduction in museums of the new information and communication technologies (NICT) as part of this process. On the one hand, these technologies open doors, and some museums take good advantage of that; but on the other hand their being used in a limited way does not enable the realisation of the role they can play, with multiple benefits from the organisational point of view, fostering innovation and creating new service concepts that are more aware of the world we live in.